Międzynarodowa ochrona korespondentów wojennych - Działak, Julita (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
In order to improve the protection of correspondents, the journalists themselves have begun to establish organizations and institutions intended to protect the reporters, or to collect and spread information. The most respectable in this respect is the International Federation of Journalists, seated in Brussels, the largest global organization of journalists. It was established in 1926. Reporters are also aided by the organization Reporters Without Borders (RWB or Reporters sans frontières – RSF) founded in 1985. On November 26, 2007 a conference was held in Geneva where the draft of an international convention on the strengthening of journalists’ protection during military conflicts and in other situations was suggested. The draft of this international Convention was subjected to global consultation